Mengapa Seniman Memahatkan Figur Raksasa Menari Pada Batur Biaro Bahal I ? (Sebuah Tinjauan Semiotika Piercian) - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2008)
AbstractIn the Piercian Semiotics, a reliefs can be seen as a system of signification that consist of, an object (called sign in Saussurean Semiotics), representamen (reference of an object), and interpretan (a new object (sign) as a result of the relation between an object and its representamen based on iconical, indexical or symbolical ground). By means of that, in order to understood why Sumateran arthist were sculpted the rakshashas figure in a dancing gesture on the base-feet of Biaro Bahal I, is by connected that reliefs with the iconical, indexical or symbolical ground that exist in their people. For example, a relation with the Vajrayana Buddhism doctrine.